Courteous Glass - Jung, Jaeyeon; Philipose, Matthai (The UbiComp workshop on usable privacy and security of wearables and domestic ubiquitous devices, 2014)
Small and always-on, wearable video cameras disrupt social norms that have been established for traditional hand-held video cameras, which explicitly signal when and which subjects are being recorded to people around the camera-holder. We first discuss privacy-related social cues that people employ when recording other people (as a camera-holder) or when being recorded by others (as a bystander or a subject). We then discuss how low-fidelity sensors such as far-infrared imagers can be used to capture these social cues and to control video cameras accordingly in order to respect the privacy of others. We present a few initial steps toward implementing a fully functioning wearable camera that recognizes social cues related to video privacy and generates signals that can be used by others to adjust their privacy expectations.